An Evaluation of Traditional Persian Medicine for the Management of SARS-CoV-2 - Bahramsoltani, Roodabeh; Rahimi, Roja (Frontiers in Pharmacology, 2020)
The new corona virus causing severe acute respiratory syndrome (SARS-CoV-2) has emerged a global attempt to investigate new antiviral treatments, as well as supportive care for organ failures due to this life-threatening viral infection. Traditional Persian Medicine (TPM) is one of the most ancient medical doctrines which is mostly known with the manuscripts of Avicenna and Rhazes. In this paper, we first introduce a series of medicinal plants potentially beneficial in SARS-CoV-2 infection according to TPM text books and then, we review the most evident medicinal plants based on the pharmacological studies available in electronic databases and discuss their mechanism of action in SARS-CoV-2 infection. There are several medicinal plants in TPM with cardiotonic, kidney tonic, and pulmonary tonic activities, protecting lung, heart, and kidney which are the three main vulnerable organs in SARS-CoV-2 infection. Also, some medicinal plants can prevent "humor infection", a situation described in TPM with similar features to SARS-CoV-2 infection. Pharmacological evaluations confirm the therapeutic activities of several plants mentioned in TPM, mostly through antiviral, cytoprotective, anti-inflammatory, antioxidant, and anti-apoptotic mechanisms. Amongst the primarily-introduced medicinal plants from TPM, rhubarb, licorice, garlic, saffron, galangal, and clove are the most studied plants which can be the candidates for clinical studies. Also, the antiviral compounds isolated from these plants provide new molecular structures to design new semisynthetic antiviral agents. Future clinical studies in healthy volunteers, as well as patients suffering from pulmonary infections are necessary to confirm the safety and efficacy of these plants as complementary and integrative intervention in SARS-CoV-2 infection.